Central SDF-1/CXCL12 expression and its cardiovascular and sympathetic effects: the role of angiotensin II, TNF-α, and MAP kinase signaling - Wei, Shun-Guang (Am J Physiol Heart Circ Physiol, 2014)
The chemokine stromal cell-derived factor-1 (SDF-1/CXCL12) and its receptors are expressed by neurons and glial cells in cardiovascular autonomic regions of the brain, including the hypothalamic paraventricular nucleus (PVN), and contribute to neurohumoral excitation in rats with ischemia-induced heart failure. The present study examined factors regulating the expression of SDF-1 in the PVN and mechanisms mediating its sympatho-excitatory effects. In urethane anesthetized rats, a 4-h intracerebroventricular (ICV) infusion of angiotensin II (ANG II) or tumor necrosis factor-α (TNF-α) in doses that increase mean blood pressure (MBP) and sympathetic drive increased the expression of SDF-1 in PVN. ICV administration of SDF-1 increased the phosphorylation of p44/42 mitogen-activated protein kinase (MAPK), JNK, and p38 MAPK in PVN, along with MBP, heart rate (HR), and renal sympathetic nerve activity (RSNA), but did not affect total p44/42 MAPK, JNK, and p38 MAPK levels. ICV pretreatment with the selective p44/42 MAPK inhibitor PD98059 prevented the SDF-1-induced increases in MBP, HR, and RSNA; ICV pretreatment with the selective JNK and p38 MAPK inhibitors attenuated but did not block these SDF-1-induced excitatory responses. ICV PD98059 also prevented the sympatho-excitatory response to bilateral PVN microinjections of SDF-1. ICV pretreatment with SDF-1 short-hairpin RNA significantly reduced ANG II- and TNF-α-induced phosphorylation of p44/42 MAPK in PVN. These findings identify TNF-α and ANG II as drivers of SDF-1 expression in PVN and suggest that the full expression of their cardiovascular and sympathetic effects depends upon SDF-1-mediated activation of p44/42 MAPK signaling.